From outsourcing to Cloud computing: Evolution of IT services - Dhar, S. (2011 IEEE International Technology Management Conference, 2011)
Many organizations are outsourcing their IT related services to a third party vendor for quite some time. However, the IT services industry including outsourcing is going through rapid changes with the increasing adoption of Cloud computing. This paper compares global IT outsourcing with Cloud computing along with the evolution of traditional IT services.